Comparison of Sinus Tarsi Approach with screws vs Lateral Extensile Approach with plates in Sanders Type Two and Three Calcaneal Fractures: A Non-Randomized Study - Borkar, Santosh; Munde, Rajiv; Godbole, Shrirang; Doshi, Suraj; Tahilramaney, Rhythm; Adhari, Bhushan; Ahmed, Sameed (Philippine Journal of Orthopaedics, 2026)
Background. Intra-articular calcaneal fractures, particularly of the joint depression type, present significant surgical challenges. The traditional lateral extensile approach (LEA), although providing excellent exposure, is associated with notable soft tissue complications, such as wound necrosis and infection. The sinus tarsi approach (STA), a minimally invasive technique, aims to minimize these complications while maintaining comparable outcomes. This study aimed to compare the functional, radiological outcomes, and complications of STA with cannulated cancellous (CC) screw fixation versus LEA with plating in the management of joint depression-type intra-articular Sanders Type 2 and 3 calcaneal fractures. Methodology. A prospective, non-randomized comparative study was conducted at a tertiary care center (BSTRH and MIMER Medical College, Talegaon Dabhade), involving 56 adult patients (aged >18 years) with acute (<three weeks) intra-articular joint depression (Sanders Type 2 and 3) calcaneal fractures, diagnosed via radiographs and CT scan. All surgeries were performed by a senior orthopaedic trauma surgeon with more than 10 years of experience. Patients were allocated into two groups of 28 each: Group A underwent STA with CC screw fixation, while Group B received LEA with plate fixation. Surgical intervention was performed after soft tissue readiness, followed by standard postoperative care. Patients were evaluated at one, three, six, nine, and 12 months postoperatively using the American Orthopaedic Foot and Ankle Society hindfoot score (AOFAS), Visual Analogue Scale (VAS), and radiological parameters including Bohler’s angle, Gissane angle, and calcaneal height and width. Complication rates, operative time, and hospital stay were also analyzed. Results. STA resulted in significantly shorter operative times (59.1 vs. 98.4 minutes, p < 0.001) and hospital stays (4.7 vs. 7.42 days, p < 0.001). AOFAS scores at 12 months were comparable between STA (mean 80.57) and LEA (mean 77.33). Postoperative VAS scores were significantly better in the STA group (1.67 vs. 2.04; p = 0.044). Radiographic outcomes were similar between groups. STA demonstrated fewer complications, including superficial infection (3 vs. 5), deep infection (0 vs. 2), and sural nerve injury (0 vs. 1). Conclusion. The sinus tarsi approach with cannulated screw fixation offers equivalent functional and radiological outcomes to the lateral